When we went to the zoo - Ormerod, Jan. (New York : Lothrop, Lee & Shepard, 1991)
Touring the zoo, two children pet, ride, and observe a variety of animals.
Keywords: Zoos -- Juvenile literature; Zoo animals -- Juvenile literature; Zoos; Zoo animals